2018
DOI: 10.1111/bjh.15660
|View full text |Cite
|
Sign up to set email alerts
|

Genetic predisposition to PEG‐asparaginase hypersensitivity in children treated according to NOPHO ALL2008

Abstract: a Shared last co-authorship to identify PEG-asparaginase hypersensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 48 publications
0
24
0
2
Order By: Relevance
“…63 Additionally, NOPHO ALL2008, through a genome-wide association study (GWAS), correlated several genetic variants to an increased incidence of pegaspargase hypersensitivity. 64 The Dutch Childhood Oncology Group (DCOG) ALL-10 study enrolled children ages 1-18 years with newly diagnosed ALL from 2009-2012. 65 Patients were stratified into 3 risk groups after induction therapy (standard, medium and high) and all received 8 doses of native E. coli asparaginase (5000 IU/m 2 per dose) every 3 days in induction.…”
Section: Hypersensitivity To Pegaspargasementioning
confidence: 99%
“…63 Additionally, NOPHO ALL2008, through a genome-wide association study (GWAS), correlated several genetic variants to an increased incidence of pegaspargase hypersensitivity. 64 The Dutch Childhood Oncology Group (DCOG) ALL-10 study enrolled children ages 1-18 years with newly diagnosed ALL from 2009-2012. 65 Patients were stratified into 3 risk groups after induction therapy (standard, medium and high) and all received 8 doses of native E. coli asparaginase (5000 IU/m 2 per dose) every 3 days in induction.…”
Section: Hypersensitivity To Pegaspargasementioning
confidence: 99%
“…Studies included in this review added new knowledge to genes and polymorphisms that could play a role in asparaginase toxicity. Previous studies found associations between polymorphisms in asparagine synthase (ASNS gene), human leukocyte antigens (HLA gene) (Abaji and Krajinovic, 2016) and the glutamate receptor (GRIA1 gene) and asparaginase toxicity (Lee and Yang, 2017;Lopez-Santillan et al, 2017;Hojfeldt et al, 2019).…”
Section: Genetic Variances and Toxicitymentioning
confidence: 99%
“…A GWAS by Højfeldt et al. (2019) found a significant higher risk of hypersensitivity with CCR4-NOT Transcription Complex Subunit 3 ( CNOT3) (rs73062673).…”
Section: Role Of Pharmacogenetic Variations In Chemotherapeutic Relatmentioning
confidence: 99%
“…In 2019, Højfeldt and collaborators performed a GWAS on a cohort of ALL pediatric patients treated according to the Nordic Society of Pediatric Hematology and Oncology (NOPHO) ALL2008 protocol: they analyzed 59 cases and 772 controls. Authors found an association between the intronic variant rs73062673 (T > C) in CCR4‐NOT transcription complex subunit 3 ( CNOT3 ) and asparaginase hypersensitivity (OR = 3.7, 95% CI, 2.33–5.98, p = 4.68 × 10 −8 ) (Højfeldt et al, 2019). Although they did not find the genetic contribution of HLA‐DRB1 rs17885382, this GWAS result supported the hypothesis that the regulation of HLA genes could play an important role in the development of asparaginase hypersensitivity.…”
Section: Asparaginase Induced Adverse Effectsmentioning
confidence: 99%